Government ownership and financing structure of government-linked companies (GLCs) and their performance / Marsitah Kassim - Kassim, Marsitah (2012)
The relationship between government ownership and GLCs performance has been an issue of interest among academics, investors and policy makers. This IS due to certain GLCs have been reported underperformed in their market and financial performance. Hence, the current study aims to examine the effect of government ownership on firm performance among government-linked companies (GLCs) in Malaysia. It is believed that government ownership serves as a control mechanism that lead to better company performance after controlling company characteristics and after the introduction of Transformation Program in 2005. Beside, this research examines the interaction between government ownership and financial leverage on company's performance. This study was based on a sample of 25 companies listed on Bursa Malaysia over a period from 2007 to 2010 and used ROA and ROE as performance measures. The regression analysis showed that there was no significant relationship between government ownership and company's performance. However, financial leverage appears to have significant relationship with GLCs performance only in 2007 and 2009. This finding is consistent with the argument that certain GLCs in Malaysia have been more concerned with political and social objective rather than profit maximization motivated.